Neonatal Health Care - Lee, Henry C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This issue of Children concerns healthcare delivery and research in neonatology. Several articles concern the work of the California Perinatal Quality Care Collaborative, including a history by founder Dr. Jeffrey Gould, and recent quality improvement work. Other articles concern methodological issues in neonatal research and findings of recent clinical studies.